Anomali Masa Jabatan Presiden Terhubung Dengan Bentuk Negara Republik: Pembatasan Masa Jabatan Presiden dalam Perspektif Konstitusi : Menghindari Otoritarianisme di Era Demokrasi - Mujahidah, Mujahidah; Tibaka, Leli (Constitutional Court of the Republic of Indonesia, Indonesia, 2024)
The proposal to extend the presidential term has emerged as a significant issue within Indonesia’s constitutional discourse. This study aims to examine the concept of a “presidential term anomaly” in relation to the republican form of government, employing a normative juridical approach. The findings indicate that Indonesia’s constitution implements a closed-norm framework, explicitly limiting the presidential term to two periods. Any effort to prolong this term is deemed unconstitutional unless the pertinent constitutional provisions are formally amended. More fundamentally, the limitation of the presidential term is closely tied to the republican model, wherein sovereignty resides with the people and executive power is held by a president. In a republic, governance is conducted by and for the people’s interest, necessitating that the exercise of power always aligns with the will and welfare of the broader community.